Gemcitabine-cisplatin chemotherapy plus anti-PD-L1 therapy reinvigorates antitumor immune response by reprogramming the intrahepatic cholangiocarcinoma microenvironment - Song, Yang; Huang, Shao-wei; Shu, Bo; Zhou, Ying-Xia; Dai, Wei-Dong; Sun, Bao-Ye (Frontiers in Immunology, 2025)
PurposeGemcitabine-cisplatin chemotherapy combined with anti-PD-L1 (GCP) therapy exhibits potent antitumor efficacy in patients with advanced intrahepatic cholangiocarcinoma (ICC). We aim to determine the intra-tumoral changes of ICC following GCP therapy in this study.MethodsWe performed single-cell RNA-seq (scRNA-seq) of 15 samples from 3 ICC patients receiving GCP therapy. The major findings of scRNA-seq analyses were further validated via analyzing the bulk RNA-seq data from the FU-iCCA cohort (n=244), as well as performing immunohistochemistry (IHC) and multiplex immunofluorescence (mIF) staining on a treatment-naïve tissue microarray (TMA) cohort (n=89) and a GCP-treated cohort (n=32).ResultsFor the scRNA-seq cohort, two patients achieved tumor regression and underwent liver resection after GCP combination therapy. The intra-tumoral enrichment of CCL18+ macrophages correlated with poor prognosis of ICC patients after curative resection in the TMA cohort. Reduced fractions of CCL18+ and SPP1+ macrophages were observed in the GCP-treated ICC specimens which achieved pathological response. Our scRNA-seq analyses revealed significant alterations in the tumor microenvironment following GCP therapy: tumor-infiltrating macrophages underwent a distinct antitumor phenotypic shift, transitioning from M2 toward M1 polarization; concurrently, CD8+ T cells exhibited enhanced costimulatory signaling characterized by CD81 upregulation and malignant cells demonstrated diminished immune escape characteristics alongside heightened activity in immune response-related pathways.ConclusionsOur preliminary findings reveal a generally reactivated antitumor immune response in ICC following GCP therapy, which could partly illuminate the enigmatic black box of intra-tumoral cellular states associated with treatment response.